Sex/gender analysis in systematic reviews. Critical review and recommendations - Raúl Aguilera Eguía; Olga Patricia López Soto; Ángel Roco Videla; Brenda Herrera Serna; Héctor Fuentes Barria; Lorena Gerli Candia (Medisur)
Integrating sex/gender analysis in systematic reviews is essential to understand the influence of sex and gender on health outcomes. Although historically underestimated, these variables are vital in clinical research to consolidate evidence in health, technological assessments and public policies. This study aims to explore in depth the importance and challenges of incorporating sex/gender analysis in systematic reviews, with emphasis on the benefits it brings and recommendations for future research. Sex/gender analysis allows for the detection of subtle differences in therapeutic effects, thereby enriching clinical practice and promoting the design of personalized therapies. However, its proper incorporation faces challenges, such as confusion between “sex” and “gender” and the lack of contextualized data. Despite these obstacles, it is essential to adopt and standardize it, in order to guarantee accurate assessments and reliable results, as well as to promote more equitable and patient-oriented medicine.